Advancement in Fenton-like reactions using PVA coated calcium peroxide/FeS system: Pivotal role of sulfide ion in regenerating the Fe(II) ions and improving trichloroethylene degradation. Issue 1 (February 2021) - Ali, Meesam; Zhang, Xiang; Idrees, Ayesha; Tariq, Muhammad; Danish, Muhammad; Farooq, Usman; Shan, Ali; Jiang, Xihao; Huang, Jingyao; Lyu, Shuguang
Graphical abstract: The insight mechanism of Fe(II)/nFeS activated oxidant (H2 O2, CP & PVA@CP) process for trichloroethylene degradation with prolonged benefits of PVA@CP. Highlights: TCE degradation was assessed in various oxic environments by Fe(II)/nFeS. PVA@nCP system showed a lower rate constant of 0.031 M −1 min −1 than other systems. Surface-bound radicals contributed to TCE degradation via a diffusion mechanism. Sulfur species of nFeS converted 10 % of surface Fe(III) to Fe(II). Comparing to Fe(III), Fe(II) significantly activated PVA@nCP with 91 % TCE removal. Abstract: This study demonstrated the prolonged benefits of polyvinyl-coated calcium peroxide (PVA@CP) in Fe(II)/nFeS mediated Fenton-like reaction. PVA@CP was prepared by a coating of PVA on calcium peroxide (CP) and synthesized nano-sized iron sulfide (nFeS) was characterized by scanning electron microscopy (SEM), high-resolution transmission electron microscopy (HR-TEM) with energy dispersive spectroscopy (EDS) elemental mapping, X-ray diffractometry (XRD), X-ray photoelectron spectroscopy (XPS), inductively coupled plasma optical emission spectroscopy (ICP-OES) and Fourier transmission infrared (FTIR) techniques. Trichloroethylene (TCE) degradation in various oxic environments (H2 O2, CP, or PVA@CP) was investigated using Fe(II)/nFeS, and the slowest rate constant of 0.031 M −1 min −1 with 91 % TCE removal highlighted the long-lasting effects of PVA@CP. The effect of initial solution pH revealed that the acidic condition was most favorable. PVA@CP system accumulated the least amount (6.34 mg/L) of Fe(III) than H2 O2 and CP systems. Electron paramagnetic resonance (EPR) and scavenging tests highlighted that free hydroxyl radicals (HO free ) contributed dominantly in H2 O2 system while both free and surface-bound species participated well in CP and PVA@CP systems. Moreover, the insight mechanism of regenerated Fe(II) on the nFeS surface was explored by XPS. Both oxidation and reduction of sulfur were discussed and declared that S(-II) was responsible for regenerating Fe(II). The recycling sample checked the reusability of nFeS, and 98.8 % TCE removal in actual groundwater emphasized that PVA@CP/Fe(II)/nFeS is a viable technique. In conclusion, the PVA@CP/Fe(II)/nFeS system is highly recommended for long-lasting remediation of TCE contaminated groundwater.